2011
DOI: 10.1111/j.1538-7836.2011.04229.x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble thrombomodulin in coronary heart disease: lack of an association in the MONICA/KORA case–cohort study

Abstract: There is increasing experimental evidence that endothelial dysfunction represents an important component of atherosclerotic cardiovascular disease (CVD).Thrombomodulin (TM) is an endothelial cell surface receptor for thrombin and exerts anti-coagulatory effects through thrombin-mediated activation of protein C which, in the presence of protein S, degrades factor (F)Va and FVIIIa, thereby restraining the coagulation reactions and restricting fibrin formation [1]. In spite of being mostly located on endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…Infectious agents may be involved in the initiation and/or progression of atherosclerotic lesions [ 8 ]. Roles have been suggested for a host of other factors in the etiology of atherosclerosis and of clinical events [ 9 ], including hemostatic factors [ 10 , 11 ], factors related to lipoprotein metabolism, insulin resistance [ 12 ], homocysteine [ 4 ], immune factors [ 13 ], inflammation markers [ 14 ], specific fatty acids [ 15 , 16 ], indicators of oxidative stress, and circulating markers of endothelial function such as cellular adhesion molecules and thrombomodulin [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Infectious agents may be involved in the initiation and/or progression of atherosclerotic lesions [ 8 ]. Roles have been suggested for a host of other factors in the etiology of atherosclerosis and of clinical events [ 9 ], including hemostatic factors [ 10 , 11 ], factors related to lipoprotein metabolism, insulin resistance [ 12 ], homocysteine [ 4 ], immune factors [ 13 ], inflammation markers [ 14 ], specific fatty acids [ 15 , 16 ], indicators of oxidative stress, and circulating markers of endothelial function such as cellular adhesion molecules and thrombomodulin [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, an inverse relationship between sTM and disease risk has been reported for type-2 diabetes (160) and coronary heart disease (134,185), while lower levels of sTM have been reported in the serum of patients suffering from acute cerebral infarction (113). Indeed, the more recent MONICA/KORA study demonstrates a lack of any association between sTM levels and CHD risk (75). The incongruity within these collective observations therefore illustrates the need for greater understanding of the precise functional relevance and action of sTM in serum and reinforces the importance of coanalyzing sTM levels with other thrombotic/coagulation markers (e.g., factor VIII, PAI-1) during vascular risk assessment and cohort stratification (6).…”
Section: Posttranslational Regulationmentioning
confidence: 99%
“…TM, which showed a positive association with a more favorable lifestyle pattern in our study, has been associated with cardiometabolic diseases in several studies. While increased TM levels were associated with lower risks of type 2 diabetes mellitus in the prospective MONICA/KORA study [18], no association was found between TM and the risk of coronary heart disease (CHD) in the same population [19]. Within the prospective ARIC study on the contrary, an inverse association between TM and incident CHD was observed [20].…”
Section: Discussionmentioning
confidence: 99%